2015
DOI: 10.1017/s001675681500014x
|View full text |Cite
|
Sign up to set email alerts
|

Is there a time lag between the metamorphism and emplacement of plutons in the Axial Zone of the Pyrenees?

Abstract: Detailed petrographic and geochemical studies conducted on zircons from the Lys-Caillaouas pluton reveal their igneous and metamorphic affinities. The igneous zircons constrain the emplacement of the pluton to 300±2 Ma. By contrast, the metamorphic zircons yield an older age of 307±3 Ma, which probably dates the thermal peak of the HT/LP Variscan metamorphism. Therefore, a short time lag of c. 7 Ma emerges between the metamorphic climax and emplacement of the pluton in the Axial Zone (Pyrenees).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 28 publications
3
30
0
8
Order By: Relevance
“…320 Ma; e.g., Aguilar et al, 2014), whereas bulk inhomogeneous transpression and syn-kinematic pluton emplacements in the superstructure lasted from ∼310 to 290 Ma. This geochronological overlap is also documented at the scale of specific domes/plutons such as the Lys-Caillaouas dome (Esteban et al, 2015), La Jonquera pluton (Aguilar et al, 2015) and the Aston dome (Denèle et al, 2009(Denèle et al, , 2014 Fig. 2).…”
Section: Structural Synthesismentioning
confidence: 80%
See 3 more Smart Citations
“…320 Ma; e.g., Aguilar et al, 2014), whereas bulk inhomogeneous transpression and syn-kinematic pluton emplacements in the superstructure lasted from ∼310 to 290 Ma. This geochronological overlap is also documented at the scale of specific domes/plutons such as the Lys-Caillaouas dome (Esteban et al, 2015), La Jonquera pluton (Aguilar et al, 2015) and the Aston dome (Denèle et al, 2009(Denèle et al, , 2014 Fig. 2).…”
Section: Structural Synthesismentioning
confidence: 80%
“…Those later authors interpreted the ∼340 Ma (Visean) ages as that of an inherited crustal component in those granites instead of that of their magmatic crystallization. Esteban et al (2015) distinguished two U-Pb zircon age groups in the Lys-Caillaouas pluton (Fig. 2) intruding the roof of the infrastructure at 307 ± 3 Ma and 300 ± 2 Ma, and suggested that the first group dated metamorphism and the second pluton crystallization.…”
Section: Pszmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the “deep‐seated” granitoids have provided two well‐differentiated isotopic ages using U–Pb zircon/monazite dating: Late Carboniferous ages. An age of 306 ± 2 Ma (U–Pb LA‐ICP‐MS) found by Denèle et al () in the Ax‐les‐Thermes granitoid (Aston dome), and another of 300 ± 2 Ma (U–Pb SIMS SHRIMP) by Esteban et al () in two facies of the Lys‐Caillaouas granitoid (Lys‐Caillaous Massif). Early Carboniferous (Visean) ages of ca. 337–339 Ma (U–Pb LA‐ICP‐MS) found by Mezger and Gerdes () in the Saulcen (Aston dome) and different facies of the Bossòst granitoids (Garona Dome). The disagreement in the age of emplacement of these granitoids is odd since it is always related to similar deformation and metamorphic events along the Axial Zone (Denèle et al, ; Hilario, ; Mezger & Passchier, ; Mezger & Gerdes, ).…”
Section: Introductionmentioning
confidence: 86%